Effect of eight week roller-ski sprint training on anaerobic power and strength in junior cross country skiers - Altunsoy, M.; Yarim, I.; Cetin, E.; Oz, E. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Aim of a training program is to increase the performance of an athlete according to needs of the chosen sport by a personalised and effective training regime (Stoggl et al., 2009). Roller skiing is similar to cross country (XC) skiing with the advantage of practising it on regular training course and at any weather condition (Cetin & Yarim, 2006).